Dataset for: Costing of sweetpotato breeding pipelines by CIP and NARS programs in sub-Sahara Africa, 2024 - Makunde, G.S.; Gonzaga, L.; Ssali, R.T.; Yada, B.; Mtonga, A.; Serenje, G.; Odiyo, O.; Musundire, L. (2025)
Costing breeding program involves running a crop breeding activity, or an entire breeding pipeline, using the prices, costs and salaries from a single year. Market segments or breeding pipelines are costed independently. In 2024, CIP in Uganda and Mozambique as well as NARS programs namely Zambia, Malawi and Uganda costed their breeding programs. Each program costed three pipelines active in their breeding programs, White Flesh, Orange Flesh and Purple Flesh pipelines. Results are available. In addition, costing of the Orange Flesh pipeline is on-going in Mozambique by the NARS program. The White Flesh pipeline has the largest market value followed by the Orange Flesh. Estimating the cost of crop breeding and its associated research activities help breeders make decisions about resource allocation depending on strategy and technology in use. In addition, costing helps in aligning breeding resources with the business market segments.